2020
DOI: 10.2196/preprints.23696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Social Media Use With Mental Health Conditions of Nonpatients During the COVID-19 Outbreak: Insights from a National Survey Study (Preprint)

Abstract: BACKGROUND Considerable research has been devoted to examining the mental health conditions of patients with COVID-19 and medical staff attending to these patients during the COVID-19 pandemic. However, there are few insights concerning how the pandemic may take a toll on the mental health of the general population, and especially of nonpatients (ie, individuals who have not contracted COVID-19). OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Besides the pandemic factors, public anxiety levels are also largely influenced by the infodemic factors, especially in the highly developed information technology era. Researchers found that the excessive social media use leads to increased levels of stress, anxiety, and vicarious trauma (35). An online survey indicated a positive link between information exposure during the COVID-19 pandemic and the occurrence of anxiety and insomnia symptoms, and the strength of the association increases with the duration of the media exposure (12,36).…”
Section: Infodemic Vs Pandemic Factors Of Public Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the pandemic factors, public anxiety levels are also largely influenced by the infodemic factors, especially in the highly developed information technology era. Researchers found that the excessive social media use leads to increased levels of stress, anxiety, and vicarious trauma (35). An online survey indicated a positive link between information exposure during the COVID-19 pandemic and the occurrence of anxiety and insomnia symptoms, and the strength of the association increases with the duration of the media exposure (12,36).…”
Section: Infodemic Vs Pandemic Factors Of Public Anxietymentioning
confidence: 99%
“…Media could be another source of vicarious trauma (48), when audiences indirectly experience the traumatic events via the vividly presented videos, pictures, and texts exposed by the media. Studies showed that obtaining more informational support via social media increased users' vicarious trauma levels (35). When the information and media content are perceived as threatening, aversive emotions can be elicited (49)(50)(51)(52), and when information is contradictory or uncertain, the distress may be even more elevated (53,54).…”
Section: Media Vicarious Traumatizationmentioning
confidence: 99%